2022
DOI: 10.1017/s0143814x22000277
|View full text |Cite
|
Sign up to set email alerts
|

Greenwashing and public demand for government regulation

Abstract: Environmental governance in many high-income democracies relies to some extent on self-regulation by the private sector. Yet, this policy mode is contested and proponents of top-down government regulation argue that voluntary corporate sustainability commitments remain shallow and rarely are more than greenwashing. I assess to what extent firms’ business conduct is subject to societal checks and balances, in particular, whether public support for regulation constitutes a control mechanism of corporate contribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
1
0
Order By: Relevance
“…The confusing and contradictory landscape of corporate environmental certification has led to growing calls for strong government regulation to ensure that sustainability advertising and communication is accurate and reliable (Kolcava, 2023). To address this, the European Union has recently adopted a proposed new law (the Directive on Green Claims) that will require all businesses to evidence and justify all environmental claims made about their products or services.…”
Section: Greenwashing Geography Power and Politicsmentioning
confidence: 99%
“…The confusing and contradictory landscape of corporate environmental certification has led to growing calls for strong government regulation to ensure that sustainability advertising and communication is accurate and reliable (Kolcava, 2023). To address this, the European Union has recently adopted a proposed new law (the Directive on Green Claims) that will require all businesses to evidence and justify all environmental claims made about their products or services.…”
Section: Greenwashing Geography Power and Politicsmentioning
confidence: 99%
“…It was found that political concepts that call for transparency on the part of companies are not sufficient to motivate companies to make deeper commitments with regard to environmental requirements. Measures such as monitoring and regulations in environmental policy (Kolcava, 2023).…”
Section: Nonmarket External Driversmentioning
confidence: 99%
“…Another factor can be dynamic inconsistency, which can lead to greenwashing if there is a discrepancy between the company's long-term environmental goals in the past and environmental sustainability in the present (Delmas & Burbano, 2011). If greenwashing is experienced by customers during shopping, the perception of risk leads 54.7% of consumers not to make a repeat purchase and the perception of confusion leads 63.4% of consumers not to make a repeat purchase (Kolcava, 2023).…”
Section: Psychological Driversmentioning
confidence: 99%
“…It was found that political concepts that call for transparency on the part of companies are not sufficient to motivate companies to make deeper commitments with regard to environmental requirements. Measures such as monitoring and regulations in environmental policy (Kolcava, 2023).…”
Section: Nonmarket External Driversmentioning
confidence: 99%
“…Another factor can be dynamic inconsistency, which can lead to greenwashing if there is a discrepancy between the company's long-term environmental goals in the past and environmental sustainability in the present (Delmas & Burbano, 2011). If greenwashing is experienced by customers during shopping, the perception of risk leads 54.7% of consumers not to make a repeat purchase and the perception of confusion leads 63.4% of consumers not to make a repeat purchase (Kolcava, 2023).…”
Section: Psychological Driversmentioning
confidence: 99%